2022
DOI: 10.3390/buildings12030345
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Simulations on Spatio-Temporal Changes of Settlement Outdoor Thermal Environment in Guanzhong Area, China

Abstract: This paper aims to provide data support for rural sustainable development through analyzing the spatio-temporal characteristics of the interactions of the outdoor thermal environment. The ordinary and representative rural settlements in the Guanzhong area were selected to analyze the dynamic process of the rural thermal environment through field measurements and numerical simulations. RMSE (root mean square error) and MAPE (mean absolute percentage) were used to verify the numerical simulation model, and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In many rural revitalization cases in Weihai, there is a common trend of using treated wood for aesthetic purposes. Unfortunately, this practice can lead to temperature increases [89] and is challenging to maintain [90], with construction costs. Through on-site visits and discussions, it was observed that the construction cost of wood planks in Weihai ranges from RMB 270 to 700 per square meter, significantly higher than the cost of brick construction, which ranges from RMB 60 to 400 per square meter.…”
Section: The Scenic Park Is Also the Best Choice For Cooling Down Dur...mentioning
confidence: 99%
“…In many rural revitalization cases in Weihai, there is a common trend of using treated wood for aesthetic purposes. Unfortunately, this practice can lead to temperature increases [89] and is challenging to maintain [90], with construction costs. Through on-site visits and discussions, it was observed that the construction cost of wood planks in Weihai ranges from RMB 270 to 700 per square meter, significantly higher than the cost of brick construction, which ranges from RMB 60 to 400 per square meter.…”
Section: The Scenic Park Is Also the Best Choice For Cooling Down Dur...mentioning
confidence: 99%
“…Particularly, P gen is the major source of heat for the human body, which is generated in a multitude of methods, including blood circulation, skeletal muscle functioning, and chemical heat from the oxidation of nutrients consumed by the human body . The typical P gen values can be categorized based on different activity levels according to ISOEN 8996: people in relaxation, sedentary people, and standing people can generate 58, 70, 96 W m –2 of energy, respectively. , The human body absorbs sunlight when exposed to the sun, whereas inside, the sunlight absorption is negligible. P sun is the surplus heat gain of the human body under the sun, which can be calculated as follows: , P normals normalu normaln = prefix∫ 0.3 4 I A M 1.5 false( λ false) · α false( λ false) d false( λ false) where I AM1.5 (λ) is the air mass (AM) 1.5 global solar radiation spectrum, λ is the radiative wavelength, and α(λ) is the solar energy absorbance of the textiles. , Notably, the overall power density of the solar spectrum is roughly 1000 W m –2 , with a majority of it concentrated in the visible and near-IR (NIR) regions between 0.3 and 4 μm …”
Section: Basic Concept Of Thermal Comfort and The Heat Pathwaymentioning
confidence: 99%
“…61 The typical P gen values can be categorized based on different activity levels according to ISOEN 8996: people in relaxation, sedentary people, and standing people can generate 58, 70, 96 W m −2 of energy, respectively. 71,72 The human body absorbs sunlight when exposed to the sun, whereas inside, the sunlight absorption is negligible. P sun is the surplus heat gain of the human body under the sun, which can be calculated as follows: 23,53…”
Section: Basic Concept Of Thermal Comfort and The Heat Pathwaymentioning
confidence: 99%
“…In Australia, what village residents were concerned about were the economic problems of climate change and government policies [ 25 ]. Climate studies in rural areas have only been based on macro perspectives and government policies [ 13 , 26 , 27 ], but there is a lack of exploration of the mechanisms of the village microclimate.…”
Section: Introductionmentioning
confidence: 99%
“…The rural economy has been boosted and the original natural landscape of villages have been changed with rapid urbanization since China’s opening reforms from 1978 [ 26 , 28 ]. Disorderly expansion of the construction area of villages, the increase in building heights, and the expansion of impervious underlying surfaces [ 27 ] have undoubtedly caused ground-surface temperatures to rise due to the thermal properties of artificial surfaces being higher than natural surfaces [ 29 , 30 ]. This also increases the burden of global climate issues due to China owning the largest number of villages in the world, especially in the northwest.…”
Section: Introductionmentioning
confidence: 99%